Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4040/jkan.2009.39.6.818
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cell Phone Addiction Scale for Korean Adolescents

Abstract: Purpose: This study was done to develop a cell phone addiction scale for Korean adolescents. Methods: The process included construction of a conceptual framework, generation of initial items, verification of content validity, selection of secondary items, preliminary study, and extraction of final items. The participants were 577 adolescents in two middle schools and three high schools. Item analysis, factor analysis, criterion related validity, and internal consistency were used to analyze the data. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 6 publications
0
34
0
7
Order By: Relevance
“…We use the term in this paper, because it is the term used in much of the literature describing excess use of technology. Indeed, even the measurement scales used to assess this overuse have the word addiction in their titles [21,22]. We make no claims to the clinical diagnosis of smartphone addiction, as it is not currently included in the DSM-5, but instead rely on its colloquial use as a common description of behaviors that are at once reinforcing and potentially problematic.…”
Section: Amentioning
confidence: 99%
See 2 more Smart Citations
“…We use the term in this paper, because it is the term used in much of the literature describing excess use of technology. Indeed, even the measurement scales used to assess this overuse have the word addiction in their titles [21,22]. We make no claims to the clinical diagnosis of smartphone addiction, as it is not currently included in the DSM-5, but instead rely on its colloquial use as a common description of behaviors that are at once reinforcing and potentially problematic.…”
Section: Amentioning
confidence: 99%
“…Participants rated each item on a 5-point Likert scale ranging from never (1) to always (5). The IAT is a well-known instrument validated psychometrically across cultures [23,24] and the CPAS has also been used in several countries [21]. It should be noted that both scales are somewhat dated; thus, the authors made substantial changes to the items.…”
Section: Materials and Measures Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In our data analysis, we first removed items 37 and 33, which were showing overlap. Next, 15 items with a factor loading below 0.50 (1,3,11,12,13,19,20,23,24,26,31,36,39,43,45) were eliminated from the scale. As can be seen in Table 1, the result of EFA, using principal component method and Varimax rotation, shows that the resulting scale has a 26-item 4-dimensional structure explaining 56.933% of the total variance; the item factor loadings with regard to this structure ranged between 0.61 and 0.82 in the deprivation (D) subdimension, between 0.53 and 0.74 in the adverse outcomes (AO) subdimension, between 0.51 and 0.69 in the control problem (CP) subdimension, and between 0.52 and 0.74 in the interaction avoidance (IA) subdimension.…”
Section: Validity Studies Exploratory Factor Analysismentioning
confidence: 99%
“…Gunuc and Kayri (18) state that in the field of technology addiction, various forms like media, television, mobile phone, computer, and internet addictions can be found. As one form of problematic technology use, problematic mobile phone use has been referred to in the literature variously as mobile phone addiction (19,20), excessive mobile phone use (6), or problematic mobile phone use (4,8). Concerning the naming of problematic technology use, Ceyhan (21) specified negative results of internet use in the general population and indicated that using the term internet addiction in non-clinical studies was not appropriate.…”
mentioning
confidence: 99%